Estrutura populacional e biologia reprodutiva de duas espécies de Hyalella Smith, 1874 (Crustacea, Amphipoda, Hyalellidae) - Ozga, Aline Vasum (2014)
Research on aspects of a population are essential because they provide information not only about the biology of the species, but of all their connection to the environment too. The objective of this study was to characterize the population structure and reproductive biology of two species of Hyalella Smith, 1874: Hyalella sp. 1 (animals samples in nascent) and Hyalella sp. 2 (individuals sampled in weir). To this end we assessed the size of the animals, the frequency distribution by size classes of cephalothorax length (CC) and total, seasonal, monthly, and size classes of CC sex ratio, reproductive period, recruitment, sexual maturity, frequency pairing and fertility. The specimens were collected with the aid of netting for 12 months in a nascent and in a weir, located on Sítio Taqui, in the city of Palmeira das Missões, state of Rio Grande do Sul (27 °53'56 "S - 53°18 '50"W). Sex and the condition of ovigerous females were recorded and all specimens were measured as cephalothorax length (mm). Both species analyzed in this study showed frequency distribution classes bimodal in total and seasonal size in both males and females. Males had body size (cephalothorax length) bigger than females. The sex ratio favored females in the overall analysis monthly and seasonal. The reproduction was seasonal and the recruitment showed continuous and sexual maturity of males is higher than those attained with female size. Individuals of the species Hyalella sp. 1 showed higher mid body size among individuals of species Hyalella sp. 2. Couples in pre-copulatory behavior were sampled throughout the year and correlation was observed between the size of males and females in couples in pre-copulation, ie large males carry large females in both species of Hyalella. Positive correlation between cephalothorax length (CC) of the females and the number of eggs and juveniles produced and also a reduction in the number of eggs during embryonic development was observed for Hyalella sp. 1. The mean fecundity of Hyalella sp. 1 was significantly superior to Hyalella sp. 2. The number of eggs produced over the seasons remained constant in both species of Hyalella. In this study the species of Hyalella showed a different population dynamics and reproductive which may be due to the strategies adopted life and the adjustments to the type of environment in which they live.